2009
DOI: 10.1126/science.1171176
|View full text |Cite
|
Sign up to set email alerts
|

γ-Secretase Heterogeneity in the Aph1 Subunit: Relevance for Alzheimer’s Disease

Abstract: The γ-secretase complex plays a role in Alzheimer’s disease (AD) and cancer progression. The development of clinical useful inhibitors, however, is complicated by the role of the γ-secretase complex in regulated intramembrane proteolysis of Notch and other essential proteins. Different γ-secretase complexes containing different Presenilin or Aph1 protein subunits are present in various tissues. Here we show that these complexes have heterogeneous biochemical and physiological properties. Specific inactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
236
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(262 citation statements)
references
References 24 publications
12
236
1
Order By: Relevance
“…The molecular mechanism that allows Aβ43 production but not other proteolytic processes remains to be clarified, but it is likely to involve specific conformational changes of the γ-secretase complex 37 . Because Aβ42 is produced independently of Aβ43 in the presence of γ-secretase, some of the FAD-associated PS1 mutations that cause a decrease in Aβ40 without an increase in Aβ42, such as A79V, A231V, C263F, L282V, L166P and G384A 24,38 , might actually result in the elevation of Aβ43 in a manner similar to the R278I mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism that allows Aβ43 production but not other proteolytic processes remains to be clarified, but it is likely to involve specific conformational changes of the γ-secretase complex 37 . Because Aβ42 is produced independently of Aβ43 in the presence of γ-secretase, some of the FAD-associated PS1 mutations that cause a decrease in Aβ40 without an increase in Aβ42, such as A79V, A231V, C263F, L282V, L166P and G384A 24,38 , might actually result in the elevation of Aβ43 in a manner similar to the R278I mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of BACE1 activity by genetic (6)(7)(8) or pharmacologic (9-13) means strongly supports a therapeutic benefit demonstrating reductions in amyloid-b levels and rescued cognitive deficits in animal models, and several clinical trials of BACE inhibitors are under way (14). TG mice recapitulate certain features of Alzheimer disease, including amyloid-b deposition, gliosis, loss of dendritic spines, and cognitive deficits (15)(16)(17). Wild-type (WT) and TG mice underwent treatment with vehicle or BACE inhibitor, and outcome measures of amyloid pathology, brain function, and neuroinflammation were obtained through small-animal PET imaging with 18 F-FDG, 18 F-peripheral benzodiazepine receptor ( 18 F-PBR) 1, and 18 F-AV45, respectively.…”
mentioning
confidence: 99%
“…These results suggest that the binding of the subunits renders the pore structure narrower to form an enzymatically active catalytic site within the pore. Supporting this notion, Fluorescence-lifetime imaging microscopic analysis revealed that the interaction with different isoforms of Aph-1 or mutant Pen-2 affected the distance between PS1 NTF and CTF (33,34). To date, several different functions of the ␥-secretase subunits have been suggested: activity modulation, substrate recognition, trafficking, and stabilization of the enzyme (35).…”
Section: Discussionmentioning
confidence: 75%